Dialogue concerning Carlo Revelli's Il catalogo per soggetti - Cheti, Alberto (JLIS.it : Italian journal of library and information science, 2012)
Il contributo presenta, in forma dialogica, i contenuti de "Il catalogo per autori" di Carlo Revelli (1970), ripubblicato di recente. Un approccio sistematico alla catalogazione per soggetti, nel quale l'autore unisce, a una notevole esperienza pratica, un'ampia informazione teorica e storica. L'importanza dell'opera nel panorama della biblioteconomia italiana è indubbia, sia come strumento di lavoro in biblioteca e come testo di riferimento per la formazione di bibliotecari. Tutto ciò ne fa un classico della biblioteconomia italiana nel campo della catalogazione. [Testo dell'editore].This article presents, in the form of a conversation, the content of the "The Author Catalog" by Carlo Revelli, published in the '70s and recently reprinted. Carlo Revelli puts together a systematic approach to the subject cataloguing, a great experience, and a wide theoretic and historical information. The importance of this work in the context of Italian library Science is beyond doubt as it is a tool for working in library and for the training of new librarians. It is the classic cataloguing book. Despite technology advancements that undermine its application, this work keeps intact its value for the understading of subject indexing. [Publisher's Text].